SUITABILITY BENEFIT PACKAGE THAT RECEIVED BY THEPARTICIPANTS OF INSURANCE IN THE HEALTH CARECENTER UNIVERSITAS AIRLANGGA - Setiawan, Iwan; Rochmah, Thinni Nurul (Universitas Airlangga, 2015)
ABSTRACTBenefit package provided for policyholderis expected to be in accordance with policyholderâs expectations. This research aimed to evaluate the conformity of the benefit package received by policyholder in Airlangga Health Care Center.This was descriptive study with cross sectional design. Data analysis quantitative with observational data.The population was all employees of Airlangga Health Care Center. The results of this study show that the total cost of health care in the PLK-UA in 2009 amounted to IDR 1.232.974.580, while the income was IDR 1.309.680.000. Based on the result, the calculation shows that the benefit package received by policyholders is worth the premium paid in the amount of IDR 60.000 per year.These conclutionis the implementation managed care insurance system that provides maximum service to policyholders by means of giving back the premium thathas been paid by the policyholders in the form of benefit package or development of facilities and infrastructure. However,revised service package provided by Airlangga Health Care Centershould be reconsidered in order to meet the expectations of policyholders.Keywords:benefit package, health insurancepremium, policyholders